First record of the Bengal fiddler crab Uca (Austruca) bengali Crane, 1975 (Braychura: Ocypodidae) from Kuakata National Park, Bangladesh - Akash, Muntasir; Chowdhury, Gawsia Wahidunnessa (Dhaka University Journal of Biological Sciences, 2017)
Abstract not available Dhaka Univ. J. Biol. Sci. 26(2): 199-203, 2017 (July)